O processo de tomada de decisão de jurados em casos de feminicídio - Almeida, Gabriela Perissinotto de (2024)
Femicide, as well as other crimes judged by the Jury Court, must be decided by the conscience of the jurors and the dictates of justice, as provided for in Article 472 of the Code of Criminal Procedure. This margin of discretion allows jurors not to be limited to the law and evidence when deciding. However, the subjective dynamics of this decision-making process need further investigation. Therefore, the objective of this research was to understand how jurors decide cases of femicide, seeking to identify how they describe and explain the experience of judging in the Jury Court. To this end, the research had a qualitative approach, with a field research design, using participant observation as an information production technique, recorded in field diaries, besides semi-structured interviews with the jurors, who decide the crime outcomes. Considering the need to identify aspects that influence this decision-making, the materials produced were subjected to content analysis. The research concluded that aspects of the subject's singularity, such as their life experience, are inherent to their decision. Also, the jurors' perceptions of the other subjects that make up the dynamics of the Jury Court are relevant. Finally, the historical and cultural context in which jurors found themselves also influenced their decisions. From this set of elements, jurors construct representations about femicide, law and justice.